Changing values and religiosity: the case of the emerging Community movement in the Evangelical-Lutheran Church of Finland - Hannikainen, Pietari (Journal of beliefs and values, 2021)
Contrary to earlier assumptions, not (only) is religion declining in modern societies, it is taking new roles in the complex development of (late) modern societies. In empirical studies on values, religiosity has been connected primarily to traditionalist value patterns that highlight stability, traditionality and security. This article, focusing on data collected from members of a renewal movement in the Evangelical-Lutheran Church in Finland (N = 529), addresses how the 10 universal values in Schwartz’s Value Theory relate to their religiosity and theological orientations. The results of the study imply that there are several religious value patterns, and not just one. Differences in theological orientation as well as other aspects of religious belief and participation proved to have an effect on the patterns. These findings open up new directions for the study of religion, spirituality and values.